Influencing factors and optimization measures for longitudinal impulse of 20 000-tonne combined heavy-haul trains - MA Ruijie; WU Jian (机车电传动)
Based on the analysis of operation test data of several 20 000-tonne heavy haul combined trains on Shuohuang railway line, the specific reasons and influencing factors causing excessive longitudinal impulse of 20 000-tone trains were obtained, mainly including large dynamic braking force adopted by the trains during air-braking release and the improper selection of air-braking release location on the long downhill grade line, as well as the operation process of the trains on the transition section between large and small downhill, etc. Then, the optimization schemes to alleviate longitudinal impulse were proposed, such as optimizing the dynamic braking force of the train, adjusting the air-braking release location. The field application after optimization shows that the longitudinal impulse of 20 000-tonne trains travelling from Shenchinan to Ningwuxi and Diliudeng to Houwen section of Shuohuang railway line have been significantly reduced respectively, which verifies the feasibility of the optimization measures.